PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE STUDENT FACILITATOR AND EXPLAINING DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 PASAMAN - Chania, Murni; Rahmi, Rahmi; Haryono, Yulia (STKIP PGRI Sumbar, 2014)
ABSTRACT This research is motivated by the understanding of the mathematical concept of class VIII SMP 2 Pasaman low . It is estimated by the learning centered on the teachers and students are afraid to ask or an opinion on the matter is not understood . This study aims to describe the development of students understanding of mathematical concepts and determine whether students comprehension of mathematical concepts using Active Learning Model Type And Explaining Student Facilitator better understanding of mathematical concepts students with learning conventional SMP 2 class VIII student Pasaman academic year 2013/2014. This research is an experimental study . The study population was all students of class VIII SMP 2 Pasaman enrolled in the school year 2013/2014 . The samples were VIII5 grade students as the experimental class and the control class VIII6 . The research instrument is an essay test , Data analysis was performed with the help of MINITAB obtained P - value = 0.043 is less than . Thus , it can be concluded that overall progress indicator increased student understanding of mathematical concepts , and understanding of mathematical concepts that students use Active Learning Model Type And Explaining Student Facilitator better than conventional learning .